Report on evaluation of mass drug administration campaign of 2014-15 against filariasis in Raichur, Karnataka, India - Angadi, Mahabaleshwar; Motappa, Rohith (International Journal Of Community Medicine And Public Health, 2016)
Background: Mass drug administration (MDA), for control of filariasis was launched by government of India in 1996. Under this programme, all the beneficiaries in the age group of 2 to 60 years (excluding pregnant mothers, people above 60 and having other illness), will be administered tablet diethylcarbamazine (100mg) and one tablet of albendazole (400mg) once a year. In 2014 this exercise was carried out in the month of May. The objectives of the study were to review the progress of activities of single dose DEC mass administration and albendazole tablets in the selected Talukas and to make assessment of the programme implementation with respect to process and outcome indicators. Methods: After visiting the selected cluster, important landmark (temple, school, panchayat office etc.) was identified. A lane was randomly selected and house to house survey was conducted. This process was continued till we could cover about 30 houses. Results: Out of 651 population surveyed 332 (50.9%) were males and 319 (49.1%) were female, 309 people (47.4%) had taken full course, 69 (10.7%) had partially taken the drugs while 273 people (41.9%) had either not received the drugs or had not taken the tablet. 7 (1.1%) people have reported minor side effects like vomiting and dizziness. Conclusions: It has been observed that though the people have received the drug distributed not everyone has consumed the tablets. Hence instruction should be given to drug distributor that they ensure consumption of the drugs in their presence only.